Parent Ratings of Generalized and Indirect Effects of Functional Communication Training for Children with Autism Spectrum Disorder. Issue 5 (September 2022) - O'Brien, Matthew J.; Pelzel, Kelly E.; Hendrix, Nicole M.; Schieltz, Kelly M.; Miller, Kenzie; Call, Nathan A.; Tsami, Loukia; Lerman, Dorothea C.; Berg, Wendy K.; Kopelman, Todd G.; Wacker, David P.; Lindgren, Scott D.
Functional communication training (FCT) is a behavioral treatment that has been shown to reduce problem behavior and increase appropriate communication in young children with autism spectrum disorder (ASD). In this study, we assessed the effects of FCT on targeted and nontargeted problem behaviors outside of the training context, as well as parent stress, for 30 young children with ASD and their parents. Indirect measures of generalization treatment effects were administered prior to and following FCT treatment delivered via telehealth. Children demonstrated significant improvement on both targeted (measured via observation) and nontargeted (measured via checklist) problem behaviors, both within and outside of the training context, and parent stress was significantly reduced following treatment. These results suggest that the impact of FCT may extend beyond the training context for both the children being treated and the parents delivering treatment, even when generalization is not specifically programmed for during treatment.